Understanding the Relative Contributions of Sensitive and Insensitive Parent Behaviors on Infant Vaccination Pain - Badovinac, Shaylea (Children (Basel), 2018)
Parents play a critical role in supporting infants’ ability to manage strong emotions. Routine vaccinations provide an ideal context to observe the effect of parents’ behaviors on infants’ pain-related distress. Previous research in the vaccination context showed that parent sensitivity, operationalized by variables such as emotional availability and proximal soothing behaviors, is associated with infant pain-related distress behavior. However, the magnitudes of these relationships were smaller than expected given the established importance of parents in the development of distress regulation. In recent work, a reliable and valid measure to operationalize insensitive behaviors was developed. The objective of the current study was to examine the relative contribution of variables representing sensitive and insensitive behaviors to the prediction of infant pain-related distress behaviors during the reactivity and regulation phases of needle pain. Archival data was used to analyze a subsample of infants followed during their two-month, six-month, and 12-month vaccinations (n = 81). Results of regression analyses indicated that parent insensitive behaviors generally had the strongest relationships with pain outcomes across all ages, with a greater influence on regulation-phase pain-related distress behavior, rather than reactivity-phase pain-related distress behavior. Our findings support the utility of a measure of distress-promoting parent behaviors in a vaccination context, and highlight the potential value of this measure for clinicians and researchers.